The growing phenomenon of Malaysian musical theatre productions with a Buddhist theme - Loo, Fung Ying; Loo, Fung Chiat; Tee, Xiao Hao (Elsevier, 2014)
Over the past twenty years, research in Buddhist music shows development and change from liturgical chant to commercial Buddhist music. The present study examines the global wave in Buddhism by looking into the growing phenomenon of “Buddhist” musical theatre in an Islamic country – Malaysia. This paper highlights the binary between the rhetoric of Buddhism manifested in the nature of commercialized musical theatre, and the influence of popular music, a commercialized and globalized phenomenon in the transmission of Buddhism. Methods include observation, analysis and semi-structured interview. Selected musicals for analysis are Jewel of Tibet the Musical, Above the Full Moon, Prince Siddhartha the Musical and Magic Mirror the Musical. Analysis includes text, music, setting, costume, and an ethnographic account of the life experience of the audience. The findings reveal a phenomenological experience of a two-fold participation in the transmission of Buddhism between the production team and audience, and the continual global wave that changes the transmission of religion.